Effect of cement additive and curing period on some engineering properties of treated peat soil - Z.A. Rahman,; N. Sulaiman,; Sahibin Abd Rahim,; Wan Mohd Razi Idris,; Tukimat Lihan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Peat soil is characterized by its high content of decomposed organic matter. Majority of areas occupied by peatland have been developed for agriculture sectors such as pineapple cultivation and oil palm. Due to its geotechnical drawback characteristics such as highly compressibility and low shear strength, peat soil is classified as problematic soils and unstable for engineering structures. Lack of suitable and expensive price of lands, peatland will be an alternative option for future development. Prior to construction works, stabilization of peat soil should be performed to enhance its engineering characteristics. This paper presents the effect of cement and curing period on engineering properties of the cement-treated peat soil. Some engineering variables were examined including the compaction behaviour, permeability and unconfined compressive strength (UCS). The Atterberg limit test was also carried out to examine the influence of cement addition on peat soil. The cement-treated peat soils were prepared by adding varying amount of ordinary Portland cement (OPC) ranging between 0% and 40% of dry weight of peat soil. In order to examine the effect of curing, the treated samples were dried at room temperature for three and seven days while for UCS tests samples were extended to 28 days prior to testings. The results showed that the liquid limit of treated soil decreased with the increase of cement content. Maximum dry density (MDD) increased while optimum moisture content (OMC) dropped with the increase in cement content. Permeability of treated soil decreased from 6.2×10-4 to 2.4×10-4 ms-1 as cement content increase from 0% to 40%. In contrast, the UCS tests indicated an increase in uncompressive strength with the increase in cement contents and curing period. The liquid limit and permeability were also altered as curing periods were extended from three to seven days. This study concluded that geotechnical properties of peat soil can be stabilized using ordinary cement and by modification of the curing periods.